Study of composite repair on sandwich structure using automated tape laying - Mohamed Assiddiq Mohamed Sallim (2018)
The aim of the project is to study the differences in strength between damaged composites repaired using an automated tape-laying robot as compared to using conventional pre-impregnated (prepreg) composite sheets. The project consisted of four main parts, the fabrication of honeycomb sandwich specimens (with and without damages), repair and replacement of damaged composite, carrying out three-point bending test on the fabricated specimen and comparing the results of the experiment. Five different types of specimen were fabricated using HexWeb A1 honeycomb structures, which are formed from high temperature resistant aramid paper and coated with a phenolic resin, with four layers of glass-fiber prepreg on each side. Of the five types of specimen, three had their composite layers damaged and two of them were repaired with one utilizing prepreg patches while the other utilizing the automated tape-laying machine. Three-point flexural testing was conducted on the specimens using the Instron 5569 testing machine. All specimens failed mainly due to fracture of the face-sheet. Results from the experimental tests showed that the 5th type of specimen using a combination of prepreg and ATL could withstand higher loads before failure.